The effect of entrepreneurial readiness, adversity quotient, and social intelligence on employability students - Zulmi, Nizar; Tentama, Fatwa (Journal of Education and Learning (EduLearn), 2024)
Vocational high schools aim to create graduates who are ready to work, but in reality, many graduates are not ready to work at this time. Low employability is the main problem. This study aims to design and test a theoretical model of the effect of entrepreneurial readiness, adversity quotient, and social intelligence on employability in vocational high school students. The population of this study was students of class XII vocational high school "X" in Moyudan, Sleman, which consisted of 209 students. The sample in this study was 68 students selected by cluster random sampling technique. The data collection method used employability scales, entrepreneurial readiness scales, adversity quotient scales, and social intelligence scales. Data were analyzed using the structural equation model (SEM) through the Smart Partial Least Square 3.3.9 program. The results of this study are the formation of a model of the influence of entrepreneurial readiness, adversity quotient, and social intelligence on employability that is appropriate (fit) with empirical data. The adversity quotient has a positive and very significant effect on employability, while entrepreneurship readiness and social intelligence have no impact on employability. This model can be used as a valid reference in developing employability variables.